A Research Study on Vibrating Elements and Consuming Electricity in Predictive Maintenance (European Journal of Formal Sciences and Engineering, 2023)
Mechanical looseness is one of the common failures detected on machines and mechanical systems. In this research, resonance effect that is a problem for mechanical systems has been studied within perspective of mechanical looseness failure through a bearing. A test setup has been designed, built and located in laboratory environment. A bearing in the electrical motor, that is one of the elements in the test setup construction, has been chosen for acquiring data throught acoustic, vibration and electrical consumption during the test. The purpose of this research is testing condition monitoring of mechanical looseness failure and resonance for studying comparison of different predictive maintenance perspectives. The test was implemented at the electricity frequency of 40.5 Hz that forced the electrical motor through identified rotation speed. According to the analysis results, inspecting of mechanical looseness failure and resonance problem has been detected as the most effectively by vibration analysis.
Keywords: acoustic, electrical consumption, mechanical looseness, resonance, vibration